(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article examines the structural and phase changes in surface diffusion nitride-oxide coatings obtained during nitriding in a gas environment followed by oxidation of ferrite-pearlite steels in water vapor, as well as the influence of phase changes on the corrosion properties.